The Cross Cultural Adaptation and Psychometric Evaluation of the Bully Survey Swearer - Student Version (BYS-S) Indonesian version (Indian Journal of Public Health Research & Development, 2020)
Background. A valid instrument to measure the bullying in primary schools is needed to determine theactual conditions.Aim. This study aimed to adapt the BYS-S questionnaire and psychometric evaluation with a culturalapproach.Method. This psychometric testing applies the cross cultural adaptation method which consists of fivetranslation stages. Item validity was analyzed by Rank-Spearman (r) and Cronbach’s alpha (?) correlationtest and followed by tests to obtain discriminatory power and difficulty level for each item.Result. The results showed that the items had a high level of validity and reliability with some discriminatoryitems and the difficulty level of each item was very good. Discriminated and difficulty items in the form andimpact on bullying victims were higher than the bullies and bystanders.Conclusion. BYS-S questionnaire Bahasa Indonesia’s version can be considered valid and reliable and hasexcellent discriminatory and difficulty power.
Keywords: bullying questionnaire, primary school students, cross cultural adaptation, psychometric